2021
DOI: 10.20473/jbk.v10i2.2021.144-152
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis to Determine Age to Give First Birth in Women in East Java Using Extended Cox Regression

Abstract: The age of a woman when giving birth to her first child needs to be a concern because it is related to the safety of the mother and baby. A woman being too young or too old increases the risk of death for both the mother and baby. Every woman giving birth for the first time is likely to experience psychological disorders such as anxiety and excessive fear during labor, and even postpartum depression. Given the importance and possible extent of the consequences of women giving birth for the first time, this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Previous research has found that a woman's age, education, place of residence, employment status, and contraceptive use are all linked to the age at which she gives her first birth in Indonesia [ 17 ]. A previous study found that regional variations exist, particularly in Sylhet and Chittagong, where total fertility rates are significantly higher than the national average.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has found that a woman's age, education, place of residence, employment status, and contraceptive use are all linked to the age at which she gives her first birth in Indonesia [ 17 ]. A previous study found that regional variations exist, particularly in Sylhet and Chittagong, where total fertility rates are significantly higher than the national average.…”
Section: Introductionmentioning
confidence: 99%
“…Women's marriage decisions are heavily influenced by factors such as education and where they reside [ 21 ]. A previous study highlighted that educational level is significantly associated with the age at first birth [ 17 ] and education has an impact on women’s marriage decisions [ 22 ]. Lower-income women are more likely to start childbearing earlier, have more children, and experience more difficulties during childbirth [ 23 ].…”
Section: Introductionmentioning
confidence: 99%